2012
DOI: 10.1017/prp.2012.2
|View full text |Cite
|
Sign up to set email alerts
|

Social Representations of Foreign Aid: Exploring Meaning-Making in Aid Practice in Sulu, Southern Philippines

Abstract: C onceptualising foreign aid as a controversial social object, this study utilised Social Representations Theory as a social constructionist framework to understand the meanings that arise from people's social interactions in relation to foreign aid practice in a particular historical, political and social context such as the province of Sulu in Southern Philippines. Key informant interviews and group discussions with representatives of various social groups involved in the practice of foreign aid in Sulu were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…The United States Agency for International Development estimates that the losses amount to at least 20% of the annual national budget (Committee for the Evangelization of Culture, 2002). Corruption has also been cited as hampering the ability of foreign aid to deliver improvements in the country (de Guzman & Montiel, 2012).…”
Section: Workplace Corruptionmentioning
confidence: 99%
“…The United States Agency for International Development estimates that the losses amount to at least 20% of the annual national budget (Committee for the Evangelization of Culture, 2002). Corruption has also been cited as hampering the ability of foreign aid to deliver improvements in the country (de Guzman & Montiel, 2012).…”
Section: Workplace Corruptionmentioning
confidence: 99%
“…For example, Sun et al (2013) found that perceived China‐Japan intergroup concerns (about historical conflicts and about geographical border disputes) impacted on Chinese donors' willingness to come to the aid of Japanese victims of an earthquake. Evidence that perceptions of intergroup assistance offered to the ingroup are shaped by the political context also comes from the Philippines specifically: de Guzman and Montiel (2012) found that foreign aid can be interpreted by the recipients as a valuable resource, but that it can also be perceived in potentially negative terms, for example, as a profiteering enterprise.…”
Section: Political Intergroup Relations Impacting On Psychological Re...mentioning
confidence: 99%